2002
DOI: 10.4161/cbt.80
|View full text |Cite
|
Sign up to set email alerts
|

The Type IV Phosphodiesterase Inhibitor Rolipram Induces Expression Inhibitors p21Cip1 and p27Kip1, Resulting in Growth Inhibition, Increased Differentiation, and Subsequent Apoptosis of Malignant A-172 Glioma Cells

Abstract: Upregulation of the cAMP/protein kinase A (PKA) pathway has been shown to result in decreased proliferation, increased differentiation, and subsequent apoptosis of malignant glioma cells. Conventional cAMP analogs, however, are difficult to use in a clinical setting. Therefore, we investigated the effects of rolipram, a drug that has undergone clinical trials as an antidepressant and has also been proposed as a treatment for multiple sclerosis. Rolipram acts as a specific inhibitor of type IV phosphodiesterase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 32 publications
1
48
0
Order By: Relevance
“…Sustained expression of PDE4D4 by hypomethylation could thus result in decreased intracellular cAMP in specific subcellular locations, creating a potential for aberrant cell signaling and potentially neoplastic transformation. In this regard, recent studies have shown a tight association between PDE4 expression and cancer cell proliferation, including glioma cells (47), osteosarcomas (48), and chronic lymphocytic leukemia (49). Importantly, PDE4 is currently being pursued as a possible chemotherapeutic target (50).…”
Section: Discussionmentioning
confidence: 99%
“…Sustained expression of PDE4D4 by hypomethylation could thus result in decreased intracellular cAMP in specific subcellular locations, creating a potential for aberrant cell signaling and potentially neoplastic transformation. In this regard, recent studies have shown a tight association between PDE4 expression and cancer cell proliferation, including glioma cells (47), osteosarcomas (48), and chronic lymphocytic leukemia (49). Importantly, PDE4 is currently being pursued as a possible chemotherapeutic target (50).…”
Section: Discussionmentioning
confidence: 99%
“…Thus persistent activation of cAMP pathways may contribute to neoplastic transformation. In this regard, recent studies have shown a tight association between PDE4 expression and cancer cell proliferation, including glioma cells (87), osteosacromas (88) and chronic lymphocytic leukemia (89). Furthermore, PDE4 is currently being pursued as a possible chemotherapeutic target (90).…”
Section: Epigenetic Changes In Dna Methylation As a Molecular Mediatomentioning
confidence: 99%
“…For example, the archetypal PDE3-selective inhibitor cilostazol (12) and the archetypal PDE4-selective inhibitor rolipram (7) both suppress colon cancer cell motility (13), whereas inhibition PDE4 by rolipram can negatively affect chronic lymphocytic leukemia (14). Interestingly, rolipram can also induce expression of cyclin-dependent kinase (CDK) inhibitors, leading to growth inhibition and differentiation of glioma cells (15), although a high concentration of rolipram was required for these effects. The cAMP-elevating agent forskolin (16), when used at high doses, has been reported to inhibit DNA replication in lymphocytes via PKAmediated effects on p21 CIP1 , leading to dephosphorylation of the retinoblastoma protein (pRb) and disrupted tethering of proliferating cell nuclear antigen to DNA (17).…”
Section: Introductionmentioning
confidence: 99%